Meningkatkan Kemampuan Menulis Bahasa Arab dengan Metode Insya’ Muwajjah: Studi pada Santri Kelas IX - Habibi Iqbal Hidayat; Sudarmadi Putra (Lembaga Sosial Rumah Indonesia, 2023)
This research is motivated by observational data indicating that the Arabic writing skills of ninth-grade students at Ma'had Tahfidz Izzah Zamzam Surakarta for the 2023/2024 academic year are still lacking. The purpose of this research is to determine the implementation of the Insya’ Muwajjah method, the driving and inhibiting factors for the implementation of the Insya’ Muwajjah method, and to assess the effectiveness of the Insya’ Muwajjah method in improving writing skills in Arabic language learning. The research was conducted on ninth-grade students at Ma'had Tahfidz Izzah Zamzam Surakarta for the 2023/2024 academic year. The method used in this research is descriptive-qualitative research. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted using the techniques stated by Miles and Huberman, which include data collection, data reduction, data display, and decision-making or verification. The validity of the research data was checked using triangulation techniques. The research results show that the implementation of the Insya’ Muwajjah method to enhance writing skills in the Arabic language for ninth-grade students at Ma'had Tahfidz Izzah Zamzam Surakarta for the 2023/2024 academic year is considered good because 80% of the students scored above the minimum passing grade, and 20% of the students scored at the minimum passing grade, which is 60.